2000
DOI: 10.1016/s1010-7940(00)00510-8
|View full text |Cite
|
Sign up to set email alerts
|

Normothermic cardiopulmonary bypass is beneficial for cognitive brain function after coronary artery bypass grafting — a prospective randomized trial✩

Abstract: Objective cognitive P300 auditory evoked potential measurements indicate, that subclinical impairment of cognitive brain function is more pronounced in patients undergoing mildly hypothermic CPB as compared with normothermic CPB for CABG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 21 publications
2
20
0
Order By: Relevance
“…Cognitive P300 evoked potentials, a long-latency endogenous evoked potential associated with psychological processing of stimulus information, can provide a quantification of impaired cognitive brain function [9][10][11][12][13]15]. It has been also reported that P300 technique is more sensitive in detecting sub-clinical impairment of cognitive brain function than standard psychometric tests [10,13,15].…”
Section: Commentmentioning
confidence: 99%
See 3 more Smart Citations
“…Cognitive P300 evoked potentials, a long-latency endogenous evoked potential associated with psychological processing of stimulus information, can provide a quantification of impaired cognitive brain function [9][10][11][12][13]15]. It has been also reported that P300 technique is more sensitive in detecting sub-clinical impairment of cognitive brain function than standard psychometric tests [10,13,15].…”
Section: Commentmentioning
confidence: 99%
“…It has been also reported that P300 technique is more sensitive in detecting sub-clinical impairment of cognitive brain function than standard psychometric tests [10,13,15]. In addition, its high intra-individual reproducibility is further emphasized [13,15]. Therefore, P300 has been used to evaluate impaired cognitive brain dysfunction for various disorders from its beginnings in the 1980s [11].…”
Section: Commentmentioning
confidence: 99%
See 2 more Smart Citations
“…However, others have reported a favourable outcome following normothermic CPB. Objective cognitive P300 auditoryevoked potential measurements have indicated cognitive impairment following hypothermic (32 8C) bypass to be more pronounced than during normothermic (37 8C) bypass [24]. Finally, McLean and colleagues were unable to Table 2 Changes in haemodynamics and cerebral cortical oxygenation during CPB demonstrate neuroprotective effects of moderate hypothermia as compared with normothermic CPB [25].…”
Section: Discussionmentioning
confidence: 99%